Analisis Kelayakan Investasi Aplikasi Navision Bagian Produksi Menggunakan Metode Information Economics pada PT. Frina Lestari Nusantara - Hudiarto, Hudiarto; Sari, Diana; Hutama, Kresna; Yudanto, Rosalia (ComTech: Computer, Mathematics and Engineering Applications, 2011)
Investments in system and information technology applied in a company sometimes do not provide benefits comparing to the cost. Therefore, we propose to PT. Frina Lestari Nusantara to measure the economic benefits gained from the implementation of Microsoft Dynamics NAV (Microsoft Navision) using Information Economics method, so that later on the benefits obtained from the feasibility assessment on the applied Navision can be provided. The methodology used is field research and literature study. The Field research is in form of observations of product selling process, analysis of the data obtained, direct interviews and questionnaire distribution to the relevant sections. The literature study is used to find, collect and study the needed data and information using references from various media and sources. From the results it is concluded that the implementation of Navision application executed so far is pretty decent to be implemented and helps improve the company’s performance.